The antecedents of reading behavior in university libraries: a meta-analysis - Zhao, Ximei; Li, Zhihong (Frontiers in Education, 2026)
IntroductionAlthough university libraries have become important places for readers to improve their literacy, acquire knowledge, and conduct academic research, however, scholars still have limited understanding of the antecedents of reading behavior.MethodsDrawing upon a comprehensive theoretical framework, we conducted a systematic review and meta-analysis to systematically summarize and outline the key determinants of current reading behavior.ResultsThis study included 37 studies (N = 15,434), our results identified 44 antecedents and compared their differences based on the following factors: (1) internal factors (individual, motivations, and habit preferences), (2) external factors (reading environment, society and culture), and (3) contextual factors. Among them, attitude (r = 0.51) is the strongest predictor of reading intention. In addition, we conducted an exploratory analysis to determine the moderating effects of publication time, cultural background (national development level), population type, methods (sample collection and measurement methods), and reading style on the relationship between antecedents and behavior. Finally, we evaluated publication’s bias and literature quality is used to determine the robustness and scalability of the results.ConclusionWe present the first systematic meta-analysis study evidence on antecedents and reading behavior, which summarizes ample empirical knowledge about reading behavior in the literature and follows contemporary meta-analysis guidelines and best practices to produce transparent and replicable scientific discoveries. Our research findings also contribute to reading interventions and provide policy and practical implications for future research on reading promotion.